Produtividade e valor nutritivo de capim bermuda em consórcio com diferentes leguminosas - Santos, Juliano Costa dos (2012)
The objective of this research was to evaluate of three pasture-based systems (PS) with bermuda grass (BG) + forage peanut + 75Kg de N/ha; BG + common vetch + 75Kg of N/ha and BG + 150Kg de N/ha. BG was planted in 2006. The forage peanut was planted in September in BG stand with three seedlings/m²; common vetch was over seeding in BG, in respective PS. Lactating Holstein cows receiving 1% of body weight/day complementary concentrate feed, were used for evaluation. The experiment was carried out from May 2010 to May 2011. In the pre grazing cycle the forage mass (PFM) botanical and structural composition, daily dry matter accumulation rate (DMA) and stocking rate (SR) were evaluated. The experimental design used was completely randomized were performed, with three treatment (PS), two replicates (paddocks) in completely, split-plot time. Eleven grazing cycles were performed during the experimental period (360 days). To determine crude protein (CP), neutral detergent fiber (NDF), dry matter in situ digestibility (DMISD), organic matter in situ digestibility (OMISD) and total digestible nutrients (TDN) samples were collected by the hand-plucking method. The mean values of PFM, DMA, SR, were 2.5; 2.6 and 2.5 t/ha; 58; 65 and 62 Kg of DM/ha/day; 6.0; 7.6 and 6.9 animal units/ha/day for respective PS. The mean values of CP, NDF, DMISD, OMISD and TDN were; 16.4; 22.2 and 15.3%; 68.3; 65.7 and 66.3%; 68.5; 70.3 and 66.4%; 64.3; 63.2 3and 65.1%; 57.7; 58.2 and 57.8% for respective PS. Residual effects of forage legume (common vetch) were observed on DMA and bermuda grass leaf blade percentage. Similar result for PFM and SR were found between BG + common vetch + 75 kg of N/ha and BG + 150 kg of N/ha. Towards the nutritive value the PS mixed to Coastcross-1 plus common vetch showed a better performance.